2009
DOI: 10.1074/jbc.m808824200
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Interleukin-18 Ameliorates Ischemia/Reperfusion-induced Myocardial Injury

Abstract: For both men and women, ischemic heart disease is one of the leading causes of death in the United States today, and its pathobiology has been attributed to many factors, including proinflammatory cytokines. Interleukin (IL) 2 -18 is a pleiotropic cytokine belonging to the IL-1 family (1-5), whose expression is up-regulated in numerous immune, infectious, and inflammatory conditions (1-5), which may further amplify the inflammatory cascade by inducing additional cytokines, chemokines, and adhesion molecules (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 48 publications
3
101
1
1
Order By: Relevance
“…A similar increase was observed in the serum and in the post-infarcted myocardium of mice subjected to experimental ischemia followed by reperfusion (63). The rapid rise in pro-IL-18 mRNA and IL-18 protein was followed by a delayed increase in IL-18BP (62).…”
Section: Myocardial Ischemia and Infarctionsupporting
confidence: 50%
See 1 more Smart Citation
“…A similar increase was observed in the serum and in the post-infarcted myocardium of mice subjected to experimental ischemia followed by reperfusion (63). The rapid rise in pro-IL-18 mRNA and IL-18 protein was followed by a delayed increase in IL-18BP (62).…”
Section: Myocardial Ischemia and Infarctionsupporting
confidence: 50%
“…The rapid rise in pro-IL-18 mRNA and IL-18 protein was followed by a delayed increase in IL-18BP (62). The use of an IL-18-neutralizing antibody, given to the mouse 1 h before ischemia, reduced infarct size (63). Furthermore, injection of mesenchymal stem cells derived from mice overexpressing IL-18BP into the coronary artery or myocardium of rats before ischemia resulted in increased left ventricular developed pressure (LVDP), improved ejection fraction and decreased infarct size (64).…”
Section: Myocardial Ischemia and Infarctionmentioning
confidence: 99%
“…Endogenous TNF-α and IL-1 play as a mediator of inflammatory reactions, whereas, IL-10 and TGF-β have cardioprotective effects on myocardial I/R injury. Previous studies demonstrated that the blocking of pro-inflammatory cytokines or the administration of cardioprotective cytokines reduced infarct size [32][33][34][35][36][37]. On the other hand, the increases in IL-4 and IFN-γ are characteristic of the activation of iNKT cells [9].…”
Section: Myocardial I/r Injury and Cytokinesmentioning
confidence: 99%
“…Furthermore, in experimental models, proinflammatory cytokines, such as TNF-a and IL-18 [26], have been shown to significantly increase cardiac rupture and dysfunction through an increase in myocyte apoptosis and infarct size. In this study, it has been demonstrated that the expression of TNF-a and IL-18 was induced following cardiac I/R.…”
Section: Discussionmentioning
confidence: 99%